Considerations regarding the reporting and evaluation of therapeutic failure in pharmacovigilance (2019)
Introduction: Therapeutic failure is a public health problem. Although there is abundant theory, a critical review of existing definitions is required. Objective: To critically review the current concept of therapeutic failure, its classification and importance in pharmacovigilance. Materials and methods: Two independent reviewers conducted a systematic search of the existing definitions of treatment failure, as well as the classification systems described in the relevant literature. Based on this information, a critical analysis was carried out and a new consensual definition of therapeutic failure was proposed. Results: The current understanding of therapeutic failure is defective as it does not consider the decrease in drug effect in real life use compared to the premarketing period, where the estimate of efficacy is based on controlled clinical trials. Although the current classification is adequate, both the algorithm of Vaca-González et al. and other tools used to assess pharmacovigilance causality depend on the quality of the report. Conclusions: It is necessary to improve the current definitions of therapeutic failure, as well as the quality of the reports to take full advantage of the classification systems. Pragmatic clinical studies for newly marketed drugs are proposed in order to establish their true effectiveness and safety profile. © 2019, Universidad Nacional de Colombia. All rights reserved.